Proteomic analysis of chicken peripheral blood mononuclear cells after infection by Newcastle disease virus - Deng, Xiaoyu (J Vet Sci, 2014)
Characteristic clinical manifestations of Newcastle disease include leukopenia and immunosuppression. Peripheral blood mononuclear cells (PBMCs) are the main targets of Newcastle disease virus (NDV) infection. To survey changes in proteomic expression in chicken PBMCs following NDV infection, PBMC proteins from 30 chickens were separated using two-dimensional electrophoresis (2-DE) and subjected to mass spectrometry analysis. Quantitative intensity analysis showed that the expression of 78 proteins increased more than two-fold. Thirty-five proteins exhibited consistent changes in expression and 13 were identified as unique proteins by matrix assisted laser desorption ionization-time of flight mass spectrometer/mass spectrometer including three that were down-regulated and 10 that were up-regulated. These proteins were sorted into five groups based on function: macromolecular biosynthesis, cytoskeleton organization, metabolism, stress responses, and signal transduction. Furthermore, Western blot analysis confirmed the down-regulation of integrin-linked kinase expression and up-regulation of lamin A production. These data provide insight into the in vivo response of target cells to NDV infection at the molecular level. Additionally, results from this study have helped elucidate the molecular pathogenesis of NDV and may facilitate the development of new antiviral therapies as well as innovative diagnostic methods.